SimpAI: Evolutionary Heuristics for the ColorShapeLinks Board Game Competition - Fernandes, Pedro M. A. (2022)
ion of the Simplexity board game. The agent uses a highly efficient parallelized Minimax-type search, with an heuristic function composed of several partial heuristics, the balance of which was optimized with an evolutionary algorithm. SimpAI was the runner-up in the competition's most challenging session, which required an AI agent with good adaptation capabilities.